Assessing the dynamics of the average capital cost of the largest Russian companies after 2022 - S. V. Korzhnev (Вестник университета)
The dynamics of the WACC indicator of Russian real sector companies has been assessed. The purpose of the study is to assess the dynamics of the capital cost of Russian companies and how it will affect their decisions. The required return on equity has been calculated based on the data of public trading on the Moscow Interbank Currency Exchange using the CAPM model. The model uses the key rate of the Central Bank of the Russian Federation as the risk-free rate. The return on borrowed capital has been estimated based on the yield on corporate bonds. The dynamics of the average capital cost for the Russian real sector companies has been obtained. The capital cost has been declining since 2022, but since the summer of 2023 it has been growing, especially sharply for companies with a fairly high level of debt, which was caused by the increase in the key rate. Continuation of the current policy of the Central Bank of the Russian Federation and a likely further increase in the key rate may lead to a significant reduction in investments of Russian companies with high levels of debt. With the rising cost of debt capital, organizations with high levels of debt will have to spend more on servicing it and use their remaining profits to reduce debt levels, which will negatively affect their investment programs size.